Characteristic of fracture zones on the southern part of Tay Nguyen - Viet, Le Trieu; Tung, Van Duc; Chi, Vu Cao; Huong, Nguyen Thi Thanh; Luan, Nguyen Van; Nam, Dao Hai; Quynh, Bui Van (Vietnam Journal of Earth Sciences, 2016)
Based on the documents of interpretation of remote sensing images, analysis topographic maps, DEM maps, combined with geologo-geomorphological, tectonophysical materials of fielships and published document, the authors established the scheme (first steps) of the tectonic fracture zones of the Earth crust on Southern part of Tay Nguyen. On this scheme, the tectonic fractures were distributed complexly in both the scale and direction of development. Upon the distribution of tectonic fractures the study area may be divided into 2 parts: NW and SE. The NW part is charactered by existence tectonic fractures of Northeast- Southwestern, Northwest- Southeastern, sublongitudinal and sublatitudinal orientations and the NE-SW tectonic fractures somewhat are developed. Meanwhile on the SE part the tectonic fractures of NE-SW direction are developed strikingly, the NW- SE are developed weaker and the sublongitudinal and sublatitudinal fractures are very sparsely. Statictical date showing there are more than 140 tectonic fracture strips with greater 10 km in length existed in study area The intersection and concentration of the fracture zones made some junction points have high prospects for finding groundwater and also for definning the good sites for recharging water in some regions of South of Central Highlands. References Bankwiz Franz K. List et al., 1992: Processing Lineament, the third UN international training cours on remote sensing application to geological sciences. Berlin, Germany. Cao Đình Triều, Phạm Huy Long, 2002: Kiến tạo đứt gãy lãnh thổ Việt Nam. Nxb. KH&KT, Hà Nội, 208tr. Đoàn Văn Cánh, Nguyễn Thị Thanh Thủy, Đào Đình Thuần, Đặng Đức Nhận, Ngô Tuấn Tú, Đặng Đức Long, 2010: Tài nguyên nước vùng Tây Nguyên và giải pháp thu gom nước mưa, nước mặt đưa vào lòng đất bổ sung nhân tạo nước dưới đất. Tc. Địa chất, số 320 (số đặc biệt kỷ niệm 65 năm ngày truyền thống Ngành Địa chất Việt Nam), tr.188-195. Lê Triều Việt, 2005: Đặc điểm kiến trúc Tân kiến tạo Nam Trung Bộ. Tc. Các Khoa học về Trái Đất, T.27, 4, 312-321. Lê Triều Việt, Văn Đức Tùng, Nguyễn Thị Thanh Hương, Vũ Cao Chí, Đào Hải Nam, Nguyễn Văn Luân, Bùi Văn Quỳnh, 2016: Đặc điểm dập vỡ kiến tạo vùng Bắc Tây Nguyên. Tc. Địa chất, loạt A, số 356, 3-4, tr.1-13. Lê Triều Việt, Vũ Văn Chinh, Văn Đức Tùng, Nguyễn Thị Thanh Hương, Vũ Cao Chí, Nguyễn Văn Luân, Bùi Văn Quỳnh, 2013: Một số kết quả ban đầu nghiên cứu dập vỡ kiến tạo khu vực Bắc Tây Nguyên. Kỷ yếu Hội thảo “Quản lý bền vững đất và nước ứng phó với hạn hán, hoang mạc hóa và lũ lụt vùng Tây Nguyên“. Viện HL KHCNVN: 153-169, Hà Nội. Ngô Gia Thắng, 1995: Đặc điểm kiến trúc Kainozoi Việt Nam. Luận án Tiến sỹ. Lưu trữ Thư viện Quốc gia. Nguyễn Xuân Sơn, 1996: Giải đoán cấu trúc địa chất miền Nam Việt Nam theo tài liệu từ hàng không, tỷ lệ 1:200.000. Luận án Tiến sỹ. Lưu trữ Thư viện Quốc gia, Hà Nội. Phạm Văn Hùng, 2000: Xác định tính chất động học của đứt gãy bằng phân tích khe nứt kiến tạo ở khu vực Nam Trung Bộ, Tc. Các Khoa học về Trái Đất, T.22, 2, 113-119. Phạm Văn Hùng, 2002: Đặc điểm đứt gãy Tân kiến tạo khu vực Nam Trung Bộ. Luận án Tiến sỹ, Lưu trữ thư viện Quốc gia, Hà Nội. Phạm Văn Hùng, Nguyễn Trọng Yêm, 1996: Kết quả nghiên cứu cơ chế hoạt động của các phá hủy đứt gãy kiến tạo vùng cực Nam Trung Bộ trong Kainozoi. Địa chất và Tài nguyên, Tập 1, 87-100, Hà Nội. Phạm Văn Hùng, Nguyễn Trọng Yêm, 1998: Xác định vùng ảnh hưởng động lực đứt gãy tân kiến tạo Nam Trung Bộ. Tc. Các Khoa học về Trái Đất, T.20, 2, 140-144. Stephen B. Mabee, Kenneth C. Hardcastle, Donald U. Wise, 2005: A Method of Collecting and Analyzing Lineaments for Regional-Scale Fractured-Bedrock Aquifer Studies. Ground Water, Volume 32, Issue 6, pages 884-894. Trần Văn Thắng, Văn Đức Tùng, 2004: Các đới đứt gãy chính có biểu hiện hoạt động trong Kainozoi muộn trên đới kiến tạo Đà Lạt. Tc. Các Khoa học về Trái Đất, T.26, 4, 554-563. Trần Văn Thắng, Văn Đức Tùng, Nguyễn Thị Thanh Hương, 2006: Đặc điểm phát triển kiến tạo đới Đà Lạt và kế cận trong Mesozoi muộn - Kainozoi. Tc. Các Khoa học về Trái Đất, T.28, 2, 140-149. Trần Văn Trị, Vũ Khúc (đồng chủ biên), 2009: Địa chất và Tài nguyên Việt Nam. Nxb. KHTN&CN, 590tr, Hà Nội. Bản đồ địa chất và khoáng sản, tỷ lệ 1:200.000 gồm các tờ: Bản Đôn, Bến Khế, Buôn Ma Thuật, Buprang, B’lao, Đà Lạt- Cam Ranh, Giá Ray, Phan Thiết (Tổng Cục Địa chất và Khoáng sản). Cẩm nang công nghệ địa chất, 2010: Phần IX, công nghệ viễn thám. Nxb. KHTN& CN, 642tr, Hà Nội.